Comparison of mechanical properties of the Type 1 and Type 2 composite hydraulic cylinder designs: A numerical study. Issue 5 (2nd March 2023) - Coskun, Taner; Sahin, Omer Sinan
Abstract: Hydraulic cylinders can reach enormous sizes depending on the working pressure and application areas. These structures, which are typically fabricated using traditional steels, can be quite heavy, which can cause a number of issues, particularly low system efficiency and fuel performance. A Type 1 composite hydraulic cylinder (CHC) with geodesic dome trajectories was created in our earlier work, and the effects of composite material utilization on the structural weight and mechanical responses were examined. Furthermore, the applicability of the geodesic dome to the CHCs was examined, and the benefits and drawbacks of using the dome profile were found. A Type 2 CHC was created in the current study, and the structural performances of Type 1 and Type 2 CHCs were compared. In this regard, numerical analyses were done to assess the mechanical responses and structural performance of a Type 2 CHC. Additionally, utilizing response surface methodology (RSM), the design parameters were optimized. The outputs of the current study were then verified by comparing the outcomes of statistical‐based RSM and FEM examinations. As a result, the structural weights for both designs were compared with steel hydraulic cylinders of the same strength, and it was revealed that Type 1 and Type 2 CHCs were 53.78% and 38.42% lighter than steel ones, respectively. In addition, the advantages and disadvantages of the design types were discussed, and thus the optimum design was determined by considering the application areas and requirements. Abstract : Comparison of Type 2 and Type 2 hydraulic cylinders